The Effect of Celebrity Endorsers and Advertising Attractiveness on Brand Image and Purchase Decisions for Tokopedia Application Users in Samarinda - Ikawati, Kartina; Militina, Theresia; Achmad, Gusti Noorlitaria (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The increase in internet users in Indonesia creates opportunities for everyone to develop their business potential towards the online realm, especially now that everyone likes practical things without having to struggle to manage time to get their daily needs. That is one of the reasons why e-commerce is popular and growing in Indonesia.Does Celebrity Endorser affect Brand Image; Does Advertising Attractiveness affect Brand Image; Does Celebrity Endorser affect the Purchase Decision; Does Advertising Attractiveness Affect Purchase Decisions; Does Brand Image Affect Purchase Decisions This study aims to analyze and explain the influence of celebrity endorsers and advertising attractiveness on product image and purchase decisions for Tokopedia application users in Samarinda. The sample selection technique used the Total Sampling Approach with a total sample of 119 people. The data collection technique used a closed questionnaire. The analysis was carried out using Partial Least Square (PLS) with the SmartPLS application version 3.8.9 and using SPSS Version 25 to test the validity and reliability of the respondents.